The saucepan game 8.50 - Ormerod, Jan. (New York : Lothrop, Lee & Shepard Books, 1989)
Baby and cat have a lot of fun playing with a saucepan.
"First published in Great Britain by Walker Books Ltd."-- Half t.p.
Keywords: Babies -- Fiction; Cats -- Fiction; Play -- Fiction